The Effect of Hotel Taxes And Entertainment Taxes On Local Own-Source Revenue Of Yogyakarta City In 2020-2022 - Putri Arumsari; Hasim As'ari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This research was conducted to determine the effect of hotel tax and entertainment tax on the local own-source revenue (PAD) of Yogyakarta City in 2020-2022. The research was conducted at BPKAD Yogyakarta City. The research method used is quantitative, using descriptive statistical data analysis techniques with IBM SPSS 26. The data used is secondary data in a monthly time series. The population in this research are reports of the realization of hotel tax revenue, entertainment tax, and the amount of local own-source revenue of Yogyakarta City. Samples were taken using a saturated sampling technique in the form of data from all reports on the realization of hotel taxes, entertainment taxes and local own-source revenue of Yogyakarta City, covering 36 months, from January 2020 to December 2022. Data analysis was carried out using the multiple linear regression analysis method. The results of the analysis show that partially, hotel tax with sig t (0.271) > ? (0.05) and entertainment tax with sig t (0.703) > ? (0.05) do not have a significant effect on the local own-source revenue (PAD) of Yogyakarta City in 2020-2022.